IHOP_2002: ARM High Resolution Radiosonde Data. Version 1.0 - UCAR/NCAR - Earth Observing Laboratory; Atmospheric Radiation Measurement (ARM) user facility; Atmospheric Measurements Program (UCAR/NCAR - Earth Observing Laboratory, 2011)
This data set contains rawinsonde profiles from five Department of Energy (DOE) Atmospheric Radiation Measurement - Clouds and Radiation (ARM-CART) sounding stations collected during the International H2O Project 2002 (IHOP 2002). ARM soundings were released from Lamont (Central Facility), Morris (B5), Purcell (B6), and Vici (B4) OK, and Hillsboro (B1), KS. Regular releases were augmented by additional releases during intensive observing periods (IOPs). The data files consist of vertical profiles of temperature, dew point, relative humidity, u and v wind components, total wind speed, wind direction, and altitude. The vertical resolution is two seconds. This data set has been quality controlled by The Joint Office of Science Support (JOSS). Consult the README for more information.
Keywords: Upper Air; Sounding; Radiosondes; Balloons/Rockets > > RADIOSONDES > > 2516981b-e560-479d-ba96-f8edfb54efe9; Radiosondes; Earth Remote Sensing Instruments > Passive Remote Sensing > Profilers/Sounders > > RADIOSONDES > > c79ff20c-08c1-41f5-8f68-13c1b6d34ba8; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC TEMPERATURE > UPPER AIR TEMPERATURE > DEW POINT TEMPERATURE; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC WINDS > UPPER LEVEL WINDS > WIND SPEED; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC PRESSURE > ATMOSPHERIC PRESSURE MEASUREMENTS; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC TEMPERATURE > UPPER AIR TEMPERATURE > VERTICAL PROFILES; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC TEMPERATURE > UPPER AIR TEMPERATURE > BOUNDARY LAYER TEMPERATURE; EARTH SCIENCE > ATMOSPHERE > ALTITUDE > GEOPOTENTIAL HEIGHT; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC WATER VAPOR > WATER VAPOR INDICATORS > HUMIDITY > RELATIVE HUMIDITY; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC WATER VAPOR > WATER VAPOR PROFILES; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC WINDS > WIND PROFILES > WIND VELOCITY/SPEED PROFILES; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC WINDS > UPPER LEVEL WINDS > WIND DIRECTION; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC WINDS > WIND PROFILES > WIND DIRECTION PROFILES; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC WINDS > UPPER LEVEL WINDS > BOUNDARY LAYER WINDS; IHOP_2002; International H2O Project 2002